Memoirs of a geisha - Marshall, Rob.; Zhang, Ziyi, 1979-; Ohgo, Suzuka; Yeoh, Michelle, 1963-; Watanabe, Ken, 1959-; Igawa, Togo.; Beebe, Dion.; Williams, John, 1932-; Golden, Arthur, 1957-; Columbia TriStar Home Entertainment (Firm) (Culver City, Calif. : Sony Pictures Home Entertainment, 2006)
In 1929, an impoverished nine-year-old named Chiyo is sold to a geisha house in Kyoto's Gion district and subjected to cruel treatment from the owners and the head geisha Hatsumomo.
Title from container.
Based on the novel by Arthur Golden.
Originally released as a motion picture in 2005.
Special features: 11 behind-the-scenes featurettes including 'The look of a geisha', 'The music of the film', Geisha bootcamp', 'A geisha's dance'; director Rob Marshall and co-producer John DeLuca audio commentary; production audio commentary.
Director of photography, Dion Beebe ; art directors, Patrick M. Sullivan, Jr., Tomas Voth ; editor, Pietro Scalia ; original music score, John Williams ; costume designer, Colleen Atwood ; production designer, John Myhre.
Ziyi Zhang, Suzuka Ohgo, Michelle Yeoh, Ken Watanabe, Togo Igawa, Mako, Samantha Futerman, Elizabeth Sung, Thomas Ikeda, Li Gong, Tsai Chin.
Keywords: Geishas -- Japan -- Kyoto -- Drama; Social skills -- Study and teaching -- Japan -- Kyoto -- Drama; Mentoring -- Japan -- Kyoto -- Drama; Women -- Conduct of life -- Drama; Feature films; Romance drama; Historical films; Films for the hearing impaired